Myrmecophilous pygmephoroid mites (Acari: Pygmephoroidea) associated with Lasius flavus (Hymenoptera: Formicidae) in Russia - Khaustov, Alexander A. (Zootaxa, 2015)
Twenty four species of pygmephoroid mites (Acari: Pygmephoroidea: Neopygmephoridae, Scutacaridae, Microdispidae) are recorded from the ant Lasius flavus (Fabricius) or from its nests from Western Siberia and Crimea. Four of them of the genus Scutacarus Gros, 1845 (Acari: Scutacaridae), S. insolitus sp. nov., S. heterotrichus sp. nov., S. moseri sp. nov. and S. sibiriensis sp. nov. are described as new for science. Four species of scutacarid mites are recorded for the first time in Russia. The comparison of pygmephoroid mite communities associated with Lasius flavus from Crimean and West Siberian populations and notes on phoresy of pygmephoroid mites on ants are provided.